Role of Demodex folliculorum in dermatology - Dopytalska, Klaudia; Lipa, Katarzyna; Sobolewski, Piotr; Szymańska, Elżbieta; Walecka, Irena (Dermatology Review/Przegląd Dermatologiczny, 2019)
Demodex folliculorum and Demodex brevis are commensal mites residing in hair follicles and sebaceous glands on human skin, primarily in seborrhoeic areas, on the scalp, and in the external auditory canals. Demodex mites feed on exfoliated epidermal cells and substances secreted by sebaceous glands. They cause mechanical blocking of follicles, follicular hyperkeratosis, and local inflammation. The prevalence of Demodex folliculorum colonisation in the population may vary between 20% and 80% of the population, and it increases with age. Demodex infestation is more common in immunocompromised patients, after application of topical glucocorticosteroids or after immunomodulatory agents. The potential role of Demodex folliculorum mites in the pathogenesis of rosacea, perioral dermatitis, blepharitis, folliculitis, and pityriasis folliculorum has been discussed.